FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (Studi Empiris pada Perusahaan Tekstil yang Terdaftar Di BEI Periode 2011-2015) - Bella Mardhatillah Sani; Amir Hasan; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The study aims to determine the factors that affect the capital structure. The company that is used as an object which is the textile company registered in the Indonesia Stock Exchange during the period 2011-2015. The factors that affect the capital structure in this study is profitability, size of the company, company’s growth, and the risk of business. This study uses secondary data with a sample of 11 companies. Determination of the sample was made by applying purposive sampling method. The results of this study showed that the variable of size and risk of business be influential significant effect to capital structure. Meanwhile, profitability and company’s growth be influential not significant effect to capital structure.Keywords: Capital Structur, Profitability, Size, Growth, Risk.